Challenges to Democratization from the Perspective of Political Inaction: Insights into Political Disempowerment and Citizenship in the Philippines - Anthony Lawrence A. Borja; Ador R. Torneo; Ian Jayson R. Hecita (Journal of Current Southeast Asian Affairs)
Though scholarship on Philippine politics has focused on either structures or elites, political participation and inaction have become equally pertinent issues, especially in times of political change. The Philippines shows a curious juxtaposition between high levels of electoral participation in the general citizenry and mass political inaction among the majority of Filipinos outside the ballot. For this reason, we would try to make sense of this paradox by analyzing political disempowerment itself and how it is linked to political participation. Hence, we raise and address the question, what challenges do political disempowerment as political powerlessness and cynicism posit against democratization in the Philippines? The trends captured in the 2nd–5th waves of the Asia Barometer Survey suggest that political disempowerment is a vicious cycle driven by perceived dis/incentives to political participation without depoliticizing citizens. Political spectatorship is the key to understanding the virtuousness or viciousness of this cycle.